Proceedings of the 1st International Conference on Intellectuals' Global Responsibility (ICIGR 2017) 2018
DOI: 10.2991/icigr-17.2018.52
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Models to Increase Students' Analytical Thinking Skills

Abstract: Abstract---Thinking skills is a trained skill according to the Curriculum-2013, ie analytical thinking skills rather than mechanistic thinking (routine). Analytical thinking skills can be improved through a particular learning model or learning strategy. This study examines learning models that improve analytical thinking skills. The learning models include Guided Inquiry, Problem Based Learning (PBL) model, Group Investigation model, Context Based Learning Model (CBL), and Model of Analytical Thinking Skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…In table 1, it is known that almost all types of inquiry-based learning can improve analytical thinking skills. The inquiry-based learning model is one of the constructivism-based models, which means that this model prioritizes student activity in the learning process, such as building independent learning and analyzing complex information (Sartika, 2018). The independence and activeness of students in education are benchmarks for the success of inquiry-based learning because each student will have the same responsibility to contribute ideas in solving problems.…”
Section: Analytical Thinking Skills Through Inquiry-based Learningmentioning
confidence: 99%
“…In table 1, it is known that almost all types of inquiry-based learning can improve analytical thinking skills. The inquiry-based learning model is one of the constructivism-based models, which means that this model prioritizes student activity in the learning process, such as building independent learning and analyzing complex information (Sartika, 2018). The independence and activeness of students in education are benchmarks for the success of inquiry-based learning because each student will have the same responsibility to contribute ideas in solving problems.…”
Section: Analytical Thinking Skills Through Inquiry-based Learningmentioning
confidence: 99%
“…Results agree with Abernathy & Forestal (2019), Gooblar, (2016, Najafi et al, (2016), andWilliams-Brown (2015), who revealed that debates enhance students' motivation, boost their academic achievements, engage students in learning better, and increase students' brain capacity. The results contribute to the teaching and learning models aimed at developing analytical thinking in tertiary students that were outlined by Sartika (2017). These models, that are integrated in the debates training, were as follows: analytical thinking skills training process, problem-based and guided inquiry learning, group investigation and context-based learning, the MURDER strategy (Mood, Understand, Recall, Digest, Expand, Review) and the use of infographics (Information and Graphics).…”
Section: Discussionmentioning
confidence: 87%
“…The examination of the theoretical sources found that the higher-order thinking skills are developed in learners by instructional models that are based on the constructivist theory (Sartika, 2017). These instructional models are as follows: a model of guided inquiry, a Problem Based Learning (PBL) model, a group investigation model, Context-Based Learning (CBL) model, a model based on the strategy of Mood, Understand, Recall, Digest, Expand, Review (MURDER), the 4A learning models involving analysis of a phenomenon, analysis of information, analysis of data, and analysis of findings, and an infographics-based learning model (Yulina et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Models and strategies of learning that can improve analytical thinking skills (as part of HOTS) generally start from presenting the problem. The problem is formulated to be proven together with the group by looking for relevant information, observing/ experimenting, concluding the results, and communicating (Sartika, 2018). In addition, Limbach & Waugh (2010) proposed five learning criteria that could facilitate HOTS, they are as follow: (1) determine the learning objectives; (2) teach through inquiry;…”
Section: Reflectionmentioning
confidence: 99%
“…(3) practice; (4) review, refine and improve understanding; and (5) practice feedback and assess learning. The syntax in Digita-RI is relevant to the terms proposed by Sartika (2018) and Limbach & Waugh (2010). Therefore, the impact of Digita-RI is that it can improve learning outcomes at the level of High Order Thinking Skills (HOTS).…”
Section: Reflectionmentioning
confidence: 99%